2023
DOI: 10.1001/jamadermatol.2023.2162
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Diagnosed Vitiligo According to Race and Ethnicity, Age, and Sex in the US

Abstract: ImportanceVitiligo has substantial psychosocial consequences. Yet its burden is poorly established.ObjectiveTo estimate incidence and prevalence of diagnosed vitiligo across age, sex, and racial and ethnic subgroups in the US.Design, Setting, and ParticipantsThis analysis comprising a cohort study and cross-sectional study included electronic health records for health care–seeking children, adolescents, and adults across 4 US census regions. Data for the incidence analysis were obtained from January 1, 2015, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Because vitiligo may be less apparent and bothersome for those with fair skin, the true prevalence of vitiligo may be higher than what was observed in this study. 1 Similar issues may occur for those who face barriers to care. Notably, a population-based study of adults in the US found 5-fold to 10-fold higher rates of vitiligo prevalence and did not find any statistically significant differences by race and ethnicity.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Because vitiligo may be less apparent and bothersome for those with fair skin, the true prevalence of vitiligo may be higher than what was observed in this study. 1 Similar issues may occur for those who face barriers to care. Notably, a population-based study of adults in the US found 5-fold to 10-fold higher rates of vitiligo prevalence and did not find any statistically significant differences by race and ethnicity.…”
mentioning
confidence: 76%
“…In this issue of JAMA Dermatology, using the IBM Explorys database, Mastacouris et al 1 estimate the incidence and prevalence of vitiligo by race and ethnicity, age, and sex in the US. This article adds to our knowledge about the underlying epidemiology of vitiligo, particularly concerning demographic subgroups and pediatric populations.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Psoriasis (PsO) is more prevalent in Northern European nations than in East Asia ( 1 ), and vitiligo is less common among Asian Americans than individuals of other races ( 2 ). Consequently, the co-occurrence of PsO and vitiligo is frequent in Europe and the Americas but rare in Asia, especially among children under 10 years of age.…”
Section: Introductionmentioning
confidence: 99%